2010
DOI: 10.1007/s10494-010-9259-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unmixedness on Combustion Instabilities in a Lean-Premixed Gas Turbine Combustor

Abstract: The present experimental study focuses on the effects of the degree of premixing and swirl strength on combustion instabilities occurring in a lean premixed gas turbine combustor burning natural gas and air. The combustor operated at pressurized conditions with heated air. Major measurements for the investigation of premixed combustion dynamics include pressure fluctuations, flame emissions in reacting flow, and acetone fluorescence in non-reacting flow to assess the degree of premixing between fuel and air. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They concluded that the modulation of the liquid fuel is crucial to prevent combustion instabilities. Seo and Lee 18 also studied combustion instability mechanisms in a lean premixed gas turbine combustor characterized by large pressure fluctuations and excessive heat transfer. They found that the pressure oscillations are strongly coupled with variations in flame structure.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the modulation of the liquid fuel is crucial to prevent combustion instabilities. Seo and Lee 18 also studied combustion instability mechanisms in a lean premixed gas turbine combustor characterized by large pressure fluctuations and excessive heat transfer. They found that the pressure oscillations are strongly coupled with variations in flame structure.…”
Section: Introductionmentioning
confidence: 99%